2018
DOI: 10.1111/liv.13751
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease is an increasing indication for liver transplantation in the Nordic countries

Abstract: NAFLD is an increasing indication for liver transplantation in the Nordic countries. Despite more advanced liver disease, NAFLD patients have a comparable survival to other patients listed for liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 37 publications
5
37
0
4
Order By: Relevance
“…Within ANZ, NASH currently only represents approximately 12% of all transplants. Similarly, a recent analysis of the Nordic Liver Transplant Registry demonstrated that NAFLD as an indication for LT increased significantly between 1994 to 2015 but only represented 6% of adult LTs between 2011 and 2015 . It is notable that the velocity of obesity rates increased significantly in Australia after 1995 from an average increase of 3.1% per decade to a 6.0% increase per decade .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within ANZ, NASH currently only represents approximately 12% of all transplants. Similarly, a recent analysis of the Nordic Liver Transplant Registry demonstrated that NAFLD as an indication for LT increased significantly between 1994 to 2015 but only represented 6% of adult LTs between 2011 and 2015 . It is notable that the velocity of obesity rates increased significantly in Australia after 1995 from an average increase of 3.1% per decade to a 6.0% increase per decade .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent analysis of the Nordic Liver Transplant Registry demonstrated that NAFLD as an indication for LT increased significantly between 1994 to 2015 but only represented 6% of adult LTs between 2011 and 2015. (18) It is notable that the velocity of obesity rates increased significantly in Australia after 1995 from an average increase of 3.1% per decade to a 6.0% increase per decade. (1) Subsequently, there was a significant increase in NASH-related transplantation 1 decade later (Table 2), demonstrating the longterm sequelae of obesity-related liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD), affecting about 25% of the global population, 5,6 has emerged as one of the leading causes of cirrhosis and HCC. [7][8][9] HCC is associated with poor survival, especially in later stages of the disease. 10,11 Screening with hepatic ultrasound biannually to detect early forms of HCC when curative treatment is still an option is therefore recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease globally [ 1 ] and is projected to become the main indication for liver transplantation in the US in the coming decade [ 2 ] and also an increasing indication for liver transplantation in the Nordic countries [ 3 ]. Histologically, NAFLD is divided into two major subgroups, nonalcoholic fatty liver (NAFL) and nonalcoholic steatohepatitis (NASH).…”
Section: Introductionmentioning
confidence: 99%